Increasing the Accuracy of Free-Form Surface Multiaxis Milling - Sadílek, Marek; Poruba, Zdeněk; Čepová, Lenka; Šajgalík, Michal (Materials (Basel, Switzerland), 2020)
This contribution deals with the accuracy of machining during free-form surface milling using various technologies. The contribution analyzes the accuracy and surface roughness of machined experimental samples using 3-axis, 3 + 2-axis, and 5-axis milling. Experimentation is focusing on the tool axis inclination angle-it is the position of the tool axis relative to the workpiece. When comparing machining accuracy during 3-axis, 3 + 2-axis, and 5-axis milling the highest accuracy (deviation ranging from 0 to 17 μm) was achieved with 5-axis simultaneous milling (inclination angles βf = 10 to 15°, βn = 10 to 15°). This contribution is also enriched by comparing a CAD (Computer Aided Design) model with the prediction of milled surface errors in the CAM (Computer Aided Manufacturing) system. This allows us to determine the size of the deviations of the calculated surfaces before the machining process. This prediction is analyzed with real measured deviations on a shaped surface-using optical three-dimensional microscope Alicona Infinite Focus G5.
Keywords: multi axis milling; CAM system; 5-axis milling; accuracy